Learning Media in Islamic Education - Johan, Budi; Ali, Fathan Faqih; Ali, Muhammad (Indonesian Journal Publisher, 2024)
This study aims to evaluate the effectiveness of using learning media in an Islamic education environment on student engagement and understanding. The research method used is qualitative with a literature study approach. The results showed that the integration of appropriate learning media can increase students' motivation and understanding of teaching materials. The findings make an important contribution to the development of teaching methods in Islamic education, improving the quality and attractiveness of learning. The conclusion of this study indicates that the use of innovative and targeted learning media can have a positive impact on Islamic education.